How to promote the public participation in eco-compensation in transboundary river basins: A case from Planned Behavior perspective. (1st September 2021) - Li, Gen; Sun, Fengyun; Fu, Bitian; Deng, Lingzhi; Yang, Kai; Liu, Yaoyi; Che, Yue
Abstract: Ecological compensation, which is known as an effective pathway to restore ecosystems, has been widely adopted in trans-boundary river basins management. Public participation is an important determinant of the efficiency and efficacy of an eco-compensation program. However, how to motivate public participation in eco-compensation in trans-boundary basins is still a challenge. Public intention and motivation regarding ecological compensation are the determinants of public participation in ecological compensation. In this study, the theory of planned behaviour is extended to explain the motivations for public eco-compensation intention in a trans-boundary river basin. Public eco-compensation intention is measured by the contingent valuation method. The main findings show that (1) the mean willingness to pay (WTP) in the downstream area and the mean willingness to accept payment (WTA) in the upstream area are 51.08 RMB and 373.9 RMB per month per household, respectively. WTA/WTP divergence is approximately 7.32 in this study. (2) Upstream of the Taipu River Basin, behavioural attitude, subjective norms, knowledge of eco-compensation and satisfaction with government work are significant influential factors of residents' behavioural intention towards eco-compensation. In the downstream area, behavioural attitude, perceived behavioural control and risk perception are among the most significant influential factors. (3) Situation awareness can promote residents' subjective norms and perceived behavioural control in downstream areas. A pathway to promote public participation in eco-compensation is given based on residents' eco-compensation intention and motivation. Highlights: CVM and TPB model were used to measure residents' eco-compensation intention in a trans-boundary river basin. RP, SGW, KE were extended to TPB model to explain the residents' eco-compensation intention in transboundary river basins. BA, SN, KE, and SGW influence residents' eco-compensation intention in the upper reach of the Taipu river. BA, PBC, and RP influence residents' eco-compensation intention in the lower reach of the Taipu river.